This preview shows pages 1–7. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: EECS 20N: Structure and Interpretation of Signals and Systems Department of Electrical Engineering and Computer Sciences UNIVERSITY OF CALIFORNIA BERKELEY Problem Set 3 SOLUTIONS 3 1 2 1 1/2 1/4 1/812 Figure 1: f ( m ) 1 2 1 1 1 3 1 421 Figure 2: h ( m ) HW 3.1 (a) Fig. 1 and Fig. 2 show the sketch for f ( m ) and h ( m ) respectively. 1 (b) Fig. 3 and Fig. 4 show the sketch for f e ( m ) and f o ( m ) respectively. You cannot construct back f from f e only . Consider t ( m ) = f e ( m ) . Hence t ( m ) is an even function with t ( − m ) = t ( m ) . Hence, t e ( m ) = t ( m )+ t ( m ) 2 = 2 t ( m ) 2 = t ( m ) = f e ( m ) and t o ( m ) = 0 . Thus, we have found a signal t ( m ) for which t e ( m ) = f e ( m ) but t ( m ) negationslash = f ( m ) . Hence, while reconstructing from f e ( m ) , we could have guessed either of the two functions. Hence, we cannot reconstruct from f e ( m ) alone. Similarly, one can prove that f ( m ) cannot be reconstructed from f o ( m ) only . 3 1 2 1 1/ 16 1/4 1/8123 1/4 1/8 1/16 Figure 3: f e ( m ) 3 1 2 1/16 1/4 1/ 8 1 2 3 1/4 1/ 8 1/16 Figure 4: f o ( m ) 2 (c) Fig. 5 and Fig. 6 show the sketch for h u ( m ) and h d ( m ) respectively. 1 2 1 1 1 3 1 421 5 643 Figure 5: h u ( m ) 1 2 1 1 3 421 5 643 Figure 6: h d ( m ) 3 (d) Fig. 7 and Fig. 8 show the sketch for g ( m ) = f ( m − 1) and g ( m ) = f ( m + 1) respectively. 3 1 2 1 1/2 1/ 4 1/81 4 Figure 7: f ( m − 1) 1 2 1 1 /2 1/4 1/8123 Figure 8: f ( m + 1) (e) For v ( m ) = f ( − m ) , we simply flip the graph of f ( m ) about the vertical access. Figure 9 plots v ( m ) . (f) To obtain w ( m ) = f ( n − m ) , we first flip the graph of f ( m ) about the vertical access, and shift it to the right by n . Figures 10 and 11 plots w ( m ) for n = 1 and n = − 1 respectively. (g) We simply multiply a flipped and shifted version of f ( m ) (which is the same as w ( m ) ) by h ( m ) . For n < , w ( m ) = 0 for n ≥ and does not overlap with h ( m ) , so p ( m ) is 0. 454321 1 0.1 0.2 0.3 0.4 0.5 0.6 0.7 0.8 0.9 1 m v(m) Figure 9: Graph of v ( m ) = f ( − m )54321 1 2 0.2 0.4 0.6 0.8 1 m w(m) Figure 10: Graph of w ( m ) = f (1 − m ) 5 For ≤ n ≤ 3 , w ( m ) overlaps with h ( m ) at n + 1 values, where the largest nonzero value is n . Figure ?? plots p ( m ) for n = 2 ....
View
Full
Document
This note was uploaded on 04/02/2008 for the course EECS 20n taught by Professor Babakayazifar during the Spring '08 term at Berkeley.
 Spring '08
 BabakAyazifar
 Computer Science, Electrical Engineering

Click to edit the document details